2018
DOI: 10.1186/s12943-018-0852-7
|View full text |Cite
|
Sign up to set email alerts
|

Pathological bases and clinical impact of long noncoding RNAs in prostate cancer: a new budding star

Abstract: Long non-coding RNAs (lncRNAs) are functional RNAs longer than 200 nucleotides. Recent advances in the non-protein coding part of human genome analysis have discovered extensive transcription of large RNA transcripts that lack coding protein function, termed non-coding RNA (ncRNA). It is becoming evident that lncRNAs may be an important class of pervasive genes involved in carcinogenesis and metastasis. However, the biological and molecular mechanisms of lncRNAs in diverse diseases are not yet fully understood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 104 publications
(131 reference statements)
1
29
0
Order By: Relevance
“…In our study, DLX6-AS1 had a high expression high level in prostate cancer, and its silencing restricted cell proliferation, migration, and invasion of prostate cancer cells in vitro as well as lymph node metastasis in vivo. The involvement of lncRNAs in the tumorigenesis, metastasis, and prognosis or diagnosis of prostate cancer has been highlighted in a previous study (15). Consistent with present findings, the level of DLX6-AS1 was upregulated in gastric cancer, where DLX6-AS1 also promotes cell proliferation, migration and EMT (16).…”
Section: Discussionsupporting
confidence: 92%
“…In our study, DLX6-AS1 had a high expression high level in prostate cancer, and its silencing restricted cell proliferation, migration, and invasion of prostate cancer cells in vitro as well as lymph node metastasis in vivo. The involvement of lncRNAs in the tumorigenesis, metastasis, and prognosis or diagnosis of prostate cancer has been highlighted in a previous study (15). Consistent with present findings, the level of DLX6-AS1 was upregulated in gastric cancer, where DLX6-AS1 also promotes cell proliferation, migration and EMT (16).…”
Section: Discussionsupporting
confidence: 92%
“…Although aggressive treatments, such as maximal resection, adjuvant radiotherapy, and chemotherapy are used for patients with GBM, the survival rate is still difficult to improve, 15 due to the poor understanding of the pathogenesis of GBM and the lack of an effective therapeutic target. Previous studies have reported that differential genes play an important role in the pathology of tumors and may be potential therapeutic targets 16–18 . To understand and identify potential therapeutic targets in GBM, we explored the mechanisms underlying the pathogenesis of GBM in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Next-generation sequencing technologies have identified more than 58,000 lncRNAs among human transcriptome, while the number of protein-coding genes is only 21,000 [16]. A variety of lncRNAs are revealed to be deregulated and associated with patients' prognosis in several cancers including cervical cancer [17][18][19][20]. Furthermore, many lncRNAs are shown to regulate various biological aspects of cancer cells, such as cell proliferation, apoptosis, cell cycle, migration, invasion, drug-resistance, and so on [21][22][23].…”
mentioning
confidence: 99%